Effects Of IAA-Containing Bacterial Application and Dolomite Dosage Reduction on the Growth of Emprit Ginger (Zingiber officinalle Var. Amarum) on Ultisol Soils - Leana, Ni Wayan Anik; Ramadhanty, Zahra Avira; Sulistyanto, Prasmadji; Khalimi, Khamdan; Pranatayana, Ida Bagus Gde (International Journal of Biosciences and Biotechnology, 2023)
Java ginger, locally known as emprit ginger, is an herb in the rhizome category with many medicinal uses. Indonesia is one of the largest ginger producing countries in the world, however its production in 2019-2022 tends to be unstable. Marginal soil, such as ultisol, can be utilized to increase the Java ginger production. Dolomite and IAA-producing bacteria are some soil ameliorants that can be applied to improve the soil quality. This study aimed to determine the effects of IAA-producing bacterial application and dolomite dosage reduction as well as identify the bacterial isolates and the optimal dose of dolomite in white ginger cultivation on ultisol. The study employed a completely randomized two-factorial design. The observed parameters include plant height (cm), leaf area (cm 2 ), total leaf area (cm 2 ), number of leaves, number of buds, and leaf greenness. Results show that S3 bacterial isolate had significant effects on plant height, leaf area, number of leaves, and leaf greenness. The dolomite dose of 100% showed the best effects on plant height, number of leaves, and number of buds. The interactions between IAA-producing bacteria and dolomite dosage affected plant height, number of leaves, and number of buds.